PERAN PENTING HUKUM ISLAM DALAM PERATURAN HUKUM INDONESIA - Hamdan Arief Hanif; Fajar Akbar (Universitas Darunnajah Jakarta, Indonesia, 2024)
Islamic law is a topic of conversation among both practitioners and academics. Not only in His laws but also in the procedures for establishing and implementing laws using Islamic teachings. This topic is usually discussed not only in the Legal Studies program but also in every faculty, both the Faculty of Law and the Faculty of Sharia and even in other faculties. There is an assumption by some Islamic law experts who doubt that Islamic law has no place and does not fill the substance of national law. The legal system that applies in Indonesia is a mixed legal system. As a former Dutch colony, the Indonesian legal system tends to follow the civil law legal system or continental European law, however, in the formation of laws and regulations in Indonesia, the Islamic legal system also has an influence. This is because the majority of the population in Indonesia is Muslim. So, existentially, the position of Islamic law in national law is a sub-system of national law. Because of Him, Islamic law also has the opportunity to contribute to the formation and renewal of national law, although it must be acknowledged that His problems and obstacles have never ended. Muslims also have the belief that all commands will be obeyed and all prohibitions will be avoided. This belief will give rise to a unified understanding that Islamic teachings (ethical and legal values) will be applied in the implementation of state affairs. If we talk about the important role of Islamic law in legal regulation in Indonesia, it can be seen from two sides, namely first from the side of Islamic law as one of the sources of national law formation and second from the aspect of the adoption of Islamic law as positive law that applies specifically in certain legal fields. . Islamic Law and National Law also have a relationship, namely Islamic Law is part of National Law because in fact national law is a law established by the Indonesian nation and applies to the Indonesian occupation. Here the author is interested in discussing the article with the title